Influence of Exogenous Growth Regulators on the Level of Cannabinoid Content Expression, Main Selection Traits of Hemp and Manifestation of Epigenetic Effects - Piliarska, Olena (Journal of Agricultural Sciences (Belgrade), 2022)
Hemp (Cannabis sativa L.) is a sensitive species to the influence of exogenous growth regulators both in the treatment of vegetative plants and in vitro culture. NAA, IAA, 2,4-D, KIN, BAP, GA3, ascorbic and nicotinic acids of exogenous origin in the studied concentrations and doses caused a change in the content of cannabinoids in plants of variety USO 31. Ascorbic acid, auxins and GA3 significantly reduced the content of cannabinoids, whereas nicotinic acid and cytokinins increased it. As a result of triple exposure to nicotinic acid and BAP, changes in the descendants persisted, with epigenetic effects, i.e. inheritance and variability, not associated with hereditary changes in DNA nucleotide sequences. An additional method to increase the level of non-psychotropic cannabinoids may be treatment of vegetative plants with cytokinin BAP (concentration 40 mg/l, consumption rate 30 ml/m2, phase of growth and development BBCH 51), which, in contrast to high concentrations of nicotinic acid, significantly increased the content of CBD and, to a lesser extent, THC. Such selection traits of the stem as its total length, mass and fiber content, seed productivity and sex significantly increased. There is a wide range of possibilities for phytohormones of exogenous activity in regulating cannabinoid accumulation, morphogenesis of hemp plants and their productivity. Different hemp genotypes may have different responses to plant growth regulators and concentrations, which should be established in each case.